The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2009
DOI: 10.1007/s10482-009-9306-y
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic, immunosuppressive, trypanocidal and antileishmanial activities of Basidiomycota fungi present in Atlantic Rainforest in Brazil

Abstract: One hundred three Basidiomycota fungi representing 84 species and 17 families were collected from different Atlantic Rainforest in Brazil. Their basidiomes and fermentation broth extracts were screened in a bioassay panel that included three human cancer cells lines, human peripheral blood mononuclear cells (PBMCs), the enzyme trypanothione reductase (TryR) from Trypanosoma cruzi, and amastigote forms of Leishmania amazonensis. Forty-two extracts representing 21 genera and 35 species presented activities highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 18 publications
(25 reference statements)
0
11
0
Order By: Relevance
“…Like prokaryotic phyla distribution patterns among various terrestrial depths (Figure 4B), the more similar eukaryotic phyla distribution patterns among various terrestrial depths were evident in S 1 (Figure 8B) highlighted the factor that a massive tsunami hit could destroy the biodiversity within microbial ecosystems. Basidiomycota, which were found more evident in S 2 , are higher fungi that play important roles as carbon recycler and nutrient decomposer, and posed the chief source of bioactive natural products [54]–[56].…”
Section: Discussionmentioning
confidence: 99%
“…Like prokaryotic phyla distribution patterns among various terrestrial depths (Figure 4B), the more similar eukaryotic phyla distribution patterns among various terrestrial depths were evident in S 1 (Figure 8B) highlighted the factor that a massive tsunami hit could destroy the biodiversity within microbial ecosystems. Basidiomycota, which were found more evident in S 2 , are higher fungi that play important roles as carbon recycler and nutrient decomposer, and posed the chief source of bioactive natural products [54]–[56].…”
Section: Discussionmentioning
confidence: 99%
“…This case of similar MIC values suggests that these particular isolates could have the same clonal origin. Several prior studies also reported differences in the biological activities among fungal isolates of the same species (Peláez et al 1998;Rosa et al 2003Rosa et al , 2009Phongpaichit et al 2006). In addition, these results suggest that more than one strain per species should be tested when examining biological activities.…”
Section: Molecular Identification Of Endophytic Fungi With Antimicrobmentioning
confidence: 91%
“…The protocol for DNA extraction of filamentous fungi was conducted according to Rosa et al (2009). The internal transcribed spacer (ITS) domains of the rRNA gene were amplified with the universal primers ITS1 (5'-TCCGTAGGTGAACCTGCGG-3') and ITS4 (5'-TCCTCCGCTTATTGATATGC-3'), as described by White et al (1990).…”
Section: Fungal Identificationmentioning
confidence: 99%
“…TH28 have anti‐leishmanial activity and caused mortality to promastigotes of Leishmania Mexicana . However, extracts of fungi belonging to the genera Alternaria, Antarctomyces, Cadophora, Davidiella, Helgardia, Herpotrichia, Microdochium, Oculimacula , Phaeosphaeria (Santiago et al ., ), and Basidiomycota (Rosa et al ., ) inhibited the proliferation of L. amazonesis . Therefore, our aim was to study the anti‐leishmanial activity of filamentous fungi and eventually the isolation and identification of the active compound(s).…”
Section: Introductionmentioning
confidence: 99%